Hua-Tan-Sheng-Jing Decoction Treats Obesity With Oligoasthenozoospermia by Up-Regulating the PI3K-AKT and Down-Regulating the JNK MAPK Signaling Pathways: At the Crossroad of Obesity and Oligoasthenozoospermia - Dong, Yang; Zheng, Yanfei; Zhu, Linghui; Li, Tianxing; Guan, Yuanyuan; Zhao, Shipeng; Wang, Qi; Wang, Ji; Li, Lingru (Frontiers in Pharmacology, 2022)
Background: Oligoasthenozoospermia is the leading cause of male infertility, seriously affecting men's health and increasing the societal medical burden. In recent years, obesity-related oligoasthenozoospermia has attracted increased attention from researchers to find a cure. This study aimed to evaluate the efficacy of Hua-Tan-Sheng-Jing decoction (HTSJD) in treating obesity with oligoasthenozoospermia, determine its active ingredients and identify its mechanism of action. Methods: The ingredients of HTSJD were determined by combining the ultra-performance liquid chromatography with mass spectrometry (UPLC-MS/MS) and systems pharmacology approach. The common pathogenesis of obesity and oligoasthenozoospermia and the potential mechanism of HTSJD against obesity with oligoasthenozoospermia were obtained through target fishing, network construction, and enrichment analyses. Further, molecular docking of the key ingredients with the upstream receptors of the key signaling pathways of the potential mechanism was used to predict their affinity. Finally, high-fat-induced obesity with oligoasthenozoospermia rat model was constructed to determine the effects of HTSJD on semen concentration, sperm motility, body weight, and serum lipid metabolism. The key proteins were validated by immunohistochemistry (IHC). Results: Firstly, 70 effective components and 847 potential targets of HTSJD (H targets) were identified. Then, 743 common targets of obesity and oligoasthenozoospermia (O-O targets) were obtained, which were mainly enriched in the pathways related to inflammation, oxidative stress and hormone regulation. Finally, 143 common targets (H-O-O targets) for HTSJD against obesity with oligoasthenozoospermia were obtained. Combining the hub genes and the results of Gene Ontology (GO) functional and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of H-O-O targets, PI3K-AKT and MAPK signaling pathways were identified as the key pathways. Molecular docking results showed that Diosgenin, Kaempferol, Quercetin, Hederagenin, Isorhamnetin may act on the related pathways by docking EGFR, IGF1R and INSR. The animal-based in vivo experiments confirmed that HTSJD improves the sperm quality of high-fat diet-fed rats by reducing their body weight and blood lipid levels, influencing the PI3K-AKT and MAPK signaling pathways and altering the corresponding protein expressions. Conclusion: HTSJD treats obesity with oligoasthenozoospermia by up-regulating the PI3K-AKT signaling pathway and down-regulating the MAPK signaling pathway, which are at the crossroad of obesity and oligoasthenozoospermia.